P16, Ki67 and P63 staining pattern in squamous metaplasia, CIN and cervical cancer - Jacob, Anu Anna; Sundaram, A. (International Journal of Research in Medical Sciences, 2018)
Background: Persistent infection with Human Papilloma Virus (HPV) has been the main cause of squamous intra epithelial neoplasia which in turn leads to cancer. The incidence is 28.0%. Early identification of dysplasia and malignancy helps early intervention. Methods: To do Immunohistochemical staining using P16ink4a, Ki 67, and P63 in cervical squamous metaplasia, CIN I, II, III and correlate the H and E features with IHC patterns. Study was carried out in SRM Medical College Hospital and Research centre, Kattankulathur, Tamil Nadu, a descriptive study for a period of 2 years (2012 to 2014) on formalin fixed paraffin embedded tissues from cervix. H and E sections of uterine cervix were categorized into squamous metaplasia, CIN I, CIN II, CIN III and squamous cell carcinoma. 50 representative samples were subjected to Four-micrometer-thick sections and subjected to IHC using PathInsitu, using P16ink4a, Ki67 and P63. Statistics: Using SPSS for windows (V.17). Data expressed by number and percentage. Methods used were Chi square test, Screening test and ROC curve. Statistical significance was 0.05. Results: P63 has shown to be the best marker out of the three to distinguish the progression of a lesion towards dysplasia and malignancy in cervix. Ki 67 showed a specificity of 84.2% with a negative predictive value of 59.3%, and an ROC curve area of 69.2%. In this study, Ki67 showed lesser sensitivity than that of P63. Conclusions: P16 identifies HPV 16 infection in uterine cervix. Ki67 and P 63 are helpful in determining the nature of progression of lesion. High expression of Ki 67 indicates a neoplastic progression. P63 may be used to differentiate benign from malignant lesions. P16 with P63 showed good results in predicting the progression of a lesion.